2005
DOI: 10.20473/j.djmkg.v38.i4.p189-193
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of recognition about denture adhesive between Japanese and Indonesian dentists: A pilot study

Abstract: The purpose of this study was to compare cross-national differences of the recognition of denture adhesive among dentists. The design of the research was cross-cultural differences. The research was done in Japan and Indonesia. One hundred and ten dentists from Japan and Indonesia were surveyed using a questionnaire regarding knowledge/comprehension of denture adhesive (in Japanese and Indonesian versions respectively). Logistic regression model (forward stepwise method) showed that it was possible to distingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This high discrepancy (0–87%) in different countries may be due to differences in awareness about denture adhesives among patients and dentists. A recent study 16 in Tehran, Iran, among 300 dentists revealed that 16% had no knowledge about denture adhesives, and two other surveys 14,15 among Japanese (Hiroshima University) and Indonesian (Airlangga University) dentists and dental students indicated differences in understanding and clinical experience of denture adhesives between the two countries. In the current survey, 70% of the Greek and 90% of the Dutch participants reported that they did not need a denture adhesive as they managed their dentures well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This high discrepancy (0–87%) in different countries may be due to differences in awareness about denture adhesives among patients and dentists. A recent study 16 in Tehran, Iran, among 300 dentists revealed that 16% had no knowledge about denture adhesives, and two other surveys 14,15 among Japanese (Hiroshima University) and Indonesian (Airlangga University) dentists and dental students indicated differences in understanding and clinical experience of denture adhesives between the two countries. In the current survey, 70% of the Greek and 90% of the Dutch participants reported that they did not need a denture adhesive as they managed their dentures well.…”
Section: Discussionmentioning
confidence: 99%
“…pastes and cushions, have been evaluated using questionnaires in a series of clinical trials [7][8][9][10][11][12][13] . Also, the knowledge level, viewpoints and experiences with denture adhesives among dentists and dental students have been investigated [14][15][16] . There have been very few reports in the recent literature about usage of and attitudes towards denture adhesives in complete denture wearers.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Meanwhile, opinions about denture adhesives have not been consent among dental professionals yet: 1) negative attitudes; prolongation of a wearing period of ill-fitting dentures; 4 allergens and irritants to denture-bearing tissues; 5,6 2) positive attitudes; prevention of food particles impaction under the denture, reduction of unfavorable mechanical irritation, and improvement in denture stability and retention. [7][8][9][10][11] A recently published study reported that there were many differences in understanding and experience of denture adhesive in the clinic between Japanese and Indonesian dentists. Japanese dentists had more information about denture adhesives.…”
Section: Introductionmentioning
confidence: 99%